Secondary battery
Patent Information
- Application Number
- JP2022188119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-07-27
- Filing Date
- 2022-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2037-02-16
Smart Images

Figure 0007637659000007 
Figure 0007637659000008 
Figure 0007637659000009
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application was filed on February 17, 2016, July 19, 2016, and July 27, 2016. Nos. 62 / 296,286 and 62 / 364,113, filed on 2013-02-13, respectively. and 62 / 367,314, the disclosures of which are incorporated herein by reference in their entirety. It is incorporated into the body. [Background technology]
[0002] FIELD OF THEINVENTION The present application relates to the field of high energy density lithium secondary batteries. The present invention relates to a method for producing a carbon-selenium nanocomposite material and its use. The present invention also relates to immobilized selenium containing carbon and a method for producing immobilized selenium and its practical utility. One of the uses of immobilized selenium is in secondary batteries. Charge-discharge cycling can be performed at a low rate (e.g., 10C rate) with minimal levels of capacity fade. When the battery is charged at a low rate, such as a 0.1C rate, the electrochemical properties such as specific capacity are The present invention also relates to a secondary battery capable of fully recovering its functional performance.
[0003] 2. Description of Related Art As human demand for energy increases, lithium-sulfur batteries and lithium-ion batteries Secondary batteries with high mass specific energy and high volumetric energy density, such as lithium-selenium batteries, The periodic table's group 6A elements, such as sulfur and selenium, are found in lithium. The theoretical mass energy of selenium is The specific capacity (675 mAh / g) is lower than that of sulfur (1675 mAh / g). Nevertheless, selenium is more abundant than sulfur (2.07 g / cm 3 ) with a higher density (4.82g / cm 3 ) Therefore, the theoretical volumetric energy density of selenium (3253 mAh / cm 3 ) is the theoretical volumetric energy density of sulfur (3467 mAh / cm 3 At the same time, sulfur Compared to , which is closer to an electrically insulating material, selenium is electrically semiconductive and has relatively good Thus, compared to sulfur, selenium exhibits relatively high electrical conductivity even at relatively high loading levels. It is possible to exhibit a comparatively high activity level and a relatively good efficiency of use, and it is possible to use high energy and high voltage In addition, the selenium-carbon composite has excellent electrical conductivity. It is possible to obtain highly active electrode materials with further improvements over sulfur-carbon composites. can be done.
[0004] As described in Chinese Patent No. 104393304A, hydrogen selenide gas is By passing the graphene oxide through a phene dispersion, the solvent heat reduces it to graphene. On the other hand, hydrogen selenide is oxidized to selenium. The electrode material and 1.5M lithium bis(trifluoromethanesulfonate)imide (LiTFS I) / 1,3-dioxolane (DOL) + dimethyl ether (DME) (volume ratio 1:1) In combination with an ether electrolyte system, the charge specific capacity is 640 mA on the first cycle. h / g (close to the theoretical specific capacity of selenium). However, during the charge and discharge process, polyselenium The oxide ions dissolve in the electrolyte, causing a significant shuttle effect and subsequent capacity loss. At the same time, the procedure for producing the graphene oxide raw material used in this process is complicated. and is not suitable for industrial production.
[0005] Chinese Patent No. 104201389A discloses a nitrogen-containing layered porous carbon incorporating selenium. A positive electrode material for a lithium selenium battery using the composite current collector is disclosed. When preparing a porous carbon composite current collector, the nitrogen-containing conductive polymer is first applied to a paper strip. The material is deposited or grown on the surface of the substrate, followed by alkaline activation and high temperature carbonization to form a support. A nitrogen-containing layered porous carbon composite having carbon fibers as a network structure that supports the Then, a composite current collector of the nitrogen-containing layered porous carbon is further coated with a cerium oxide. The deposition process for producing conductive polymers is complex and the films The process for forming or growing the , which is associated with undesirably high costs.
[0006] In addition, electronics, electric / hybrid vehicles, aerospace / High rate charging and discharging in drones, submarines, and other industrial, military, and civilian applications There is a demand for secondary batteries with long life, high energy density, and high power density that can be charged with electricity. Lithium ion batteries are an example of secondary batteries for the above applications. The demand for greater capacity and cycling performance is not being met by lithium-ion batteries. This is because lithium-ion battery technology has matured.
[0007] The oxygen atom has an atomic weight of 16 and is capable of transferring two electrons. Lithium-ion secondary battery has been studied for the purpose of producing batteries with high energy density. When the battery contains an oxygen cathode paired with metallic lithium or metallic sodium of up to However, in the Li / Na-oxygen battery, Most of the technical problems remain unresolved.
[0008] The element sulfur also belongs to the oxygen group and is paired with metallic lithium or metallic sodium anodes. Sometimes has the second highest energy density (after oxygen). Lithium-sulfur battery or nano-battery Thorium-sulfur batteries have been widely studied. However, Li-S or Na-S batteries Polysulfide ions (intermediates) formed during the discharge process dissolve in the electrolyte and form cathodic Upon reaching the anode, the polysulfide anions react with the gold Reacting with metallic lithium or metallic sodium to produce undesirable energy for the battery system - This results in a loss of density. In addition, sulfur is an insulator and achieves the lowest level of electrical conductivity. However, a high degree of carbon loading is required for this purpose. However, Li / Na-S secondary batteries are very difficult to discharge or charge at high rates. Summary of the Invention
[0009] Disclosed herein is a method for producing two-dimensional carbon nanomaterials with a high degree of graphitization. By combining the original carbon nanomaterial with selenium, a carbon-selenium composite material was obtained. , which is used as a cathode material paired with a lithium-containing anode material, and produces high energy A lithium selenium battery with high density and stable electrochemical properties is obtained. Similar processes can be used to further assemble batteries, and pouch cells also offer excellent electrochemical properties. It shows the characteristic.
[0010] Selenium-carbon composites can be fabricated using readily available raw materials and through simple manufacturing procedures. Methods for producing the materials are also disclosed.
[0011] The selenium-carbon composite material described herein can be obtained by a manufacturing method comprising the steps of: can.
[0012] (1) After carbonizing an alkali metal organic salt or an alkaline earth metal organic salt at high temperature, it is dissolved in dilute hydrochloric acid or Wash with another acid and dry to obtain a two-dimensional carbon material.
[0013] (2) The two-dimensional carbon material obtained in step (1) is mixed with selenium in an organic solution and heated to form a The organic solvent was evaporated, and then the two-dimensional carbon material was used to perform multi-step temperature gradient and isothermal heating. Selenium is then composited to obtain a carbon-selenium composite.
[0014] In step (1), the alkali metal organic salt is potassium citrate or potassium gluconate. and sodium sucrose. The metal organic salt is selected from one or both of calcium gluconate and calcium sucrose. The high-temperature carbonization is carried out at a temperature of 600 to 1000°C, preferably 700 to 900°C. The carbonization time is 1 to 10 hours, preferably 3 to 5 hours.
[0015] In step (2), the organic solvent is ethanol, dimethyl sulfoxide (DMSO), Toluene, acetonitrile, N,N-dimethylformamide (DMF), carbon tetrachloride, and and diethyl ether, or ethyl acetate. The gradient and soaking sections are between 200°C and 300°C, preferably 220°C. and 280°C, the heating rate is 2 to 10°C / min, preferably 5 to 8°C / min. Then, the mixture is soaked for 3 to 10 hours, preferably 3 to 4 hours. Continue heating to 430-460°C, preferably 430-460°C, followed by heating for 10-30 hours, preferably 1 Soak for 5 to 20 hours.
[0016] The present specification also describes a lithium-selenium secondary battery that includes the carbon-selenium composite material. The lithium selenium secondary battery comprises a lithium-containing anode, a separator, and an electrolyte. (electrolyte).
[0017] Lithium-containing anodes include metallic lithium, lithiated graphite anode materials, and lithium Silicon-carbon anode material (graphite, silicon-carbon anode material and lithium anode) The lithium-ionized graphite anode and the lithium-ionized silicon carbon anode were then sintered to prepare a half-cell, which was then discharged. The separator (membrane) may be, but is not limited to, a cell Celgard membrane, Whatman membrane, cellulose membrane, or poly The electrolyte may be a commercially available membrane such as a polymer membrane. The electrolyte may be a carbonate electrolyte, an ether electrolyte, or a mixture of both. and ionic liquids.
[0018] Carbonate electrolytes are diethyl carbonate (DEC), dimethyl carbonate (D MC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and propylene carbonate (PC). Lithium fluoride phosphate (LiPF6), lithium bis(trifluoromethanesulfonyl) isopropyl alcohol Lithium fluoride (LiTFSI), lithium perchlorate (LiClO4), and lithium bis(fluoro) The alkyl group may be selected from one or more of the following:
[0019] In the ether electrolyte, the solvent is 1,3-dioxolane (DOL), ethylene glycol DME, and triethylene glycol dimethyl ether (TE GDME) and the solute is lithium hexafluorophosphate (LiP F6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), persalt Lithium bisfluorosulfonyl imide (LiClO4) and lithium bisfluorosulfonyl imide (LiFS One or more of the following may be selected: I).
[0020] In the ionic liquid, the ionic liquid is [EMIm]NTf2 (1-ethyl-3-methyl imidazolium bistrifluoromethanesulfonimide salt), [Pyl3]NTf2 (N-propyl-N-methylpyrrolidine bistrifluoromethanesulfonimide salt), [ PP13]NTf2 (N-propyl-methylpiperidinealkoxy-N-bistrifluoro The solute is one or more ionic liquids selected from the group consisting of fluoromethanesulfonimide salts. , Lithium hexafluorophosphate (LiPF6), Bis(trifluoromethylsulfonyl)imide Lithium tetrafluoroethylene (LiTFSI), lithium perchlorate (LiClO4), and lithium bisfluorofluoroethylene (LiTFSI). One or more of the following may be selected: sulfonylimide (LiFSI).
[0021] Also disclosed herein is a pouch-type lithium-selenium cell battery that includes a carbon-selenium composite material. do.
[0022] The method of producing the selenium carbon composite material disclosed herein is compared with the prior art. In addition, two-dimensional carbon materials are easy to obtain and have low cost raw materials, and the manufacturing process is simple and practical. The obtained selenium-carbon composite material has the advantages of being highly stable and suitable for mass production. The electrochemical properties are shown.
[0023] Also disclosed herein is an immobilized selenium body that includes selenium and a carbon skeleton. The immobilized selenium contains at least one of the following: (a) a selenium-binding protein that is released from the immobilized selenium system; ≧9.5 kJ / mol, ≧9.7 kJ / mol, ≧9.9 kJ / mol, ≧10.1 kJ / mol, ≥ 10.3 kJ / mol, or ≥ 10.5 kJ / mol (b) The selenium particles must acquire sufficient energy to react with the immobilized selenium system. In order for the selenium particles to acquire sufficient energy to detach from the 00°C, ≧510°C, ≧520°C, ≧530°C, ≧540°C, ≧550°C, or ≧560°C (c) The carbon skeleton must be at least 500 m 2 / g, ≥ 600m 2 / g, ≥ 7 00m 2 / g, ≥800m 2 / g, ≥900m 2 / g, or ≥ 1,000m 2 / g surface (d) The carbon skeleton has a surface area of less than 20 Å. Less than 15%, less than 10%, less than 5%, less than 3%, less than 2%, less than 1% of surface area (2 0 Angstroms and 1,000 Angstroms).
[0024] Also disclosed herein is a cathode or secondary battery comprising immobilized selenium. The selenium is It may also be doped with other elements, such as, but not limited to, sulfur.
[0025] Also, as used herein, the term "amorphous polymer" refers to polymers having an aspect ratio of ≧1, ≧2, ≧5, ≧10, or ≧20. Also disclosed are complexes containing selenium and carbon, including platelet forms.
[0026] Also, as used herein, the term "amorphous polymer" refers to polymers having an aspect ratio of ≧1, ≧2, ≧5, ≧10, or ≧20. A cathode comprising a composite having a platelet morphology and comprising selenium and carbon is also disclosed. The present specification provides a platelet morphology having the above aspect ratio and comprising selenium and carbon, A secondary battery comprising the composite is also disclosed.
[0027] The present specification also refers to a secondary battery including a cathode, an anode, a separator, and an electrolyte. The secondary battery is disclosed as having a capacity of 0.1C, 0.2C, 0.5C, 1C, 1.5C, 2C, and 3C. , 4C, 5C, 6C, 7C, 8C, 9C, 10C or faster. The sword is made up of at least two elements of the chalcogen group (oxygen group), including selenium, sulfur, tellurium, and oxygen. The anode may contain one element selected from the group consisting of alkali metals, alkaline earth metals, and Group IIIA elements. The separator may include at least one element of metal(s). The electrolyte may include an organic or inorganic separator, which may be modified as necessary. At least one of the alkali metals, alkaline earth metals, and group IIIA metals (one or more) The solvent in the electrolyte may be a carbonate, ether, or ester. The solvent may include an organic terephthalate solvent.
[0028] Secondary batteries: 400mAh / g or more, 450mAh / g or more, 500mAh / g or more, The secondary battery may have a specific capacity of 550 mAh / g or more, or 600 mAh / g or more. , 50 cycles or more, 75 cycles or more, 100 cycles or more, 200 cycles or more, etc. The secondary battery may be capable of undergoing an electrochemical cycle of a high C-rate charge / discharge cycle. (e.g. 5 cycles at 0.1C, 5 cycles at 0.2C, 5 cycles at 0.5C, 5 cycles at 1C, 5 cycles at 2C, 5 cycles at 5C, and 5 cycles at 10C) After that, at a cycle rate of 0.1C, the second discharge specific capacity was more than 30%. Greater than 40%, Greater than 50%, Greater than 60%, Greater than 70% A secondary battery may maintain a specific battery capacity of ≥ 50%, or ≥ 80%. The secondary battery may have a coulombic efficiency of ≧60%, ≧70%, ≧80%, or ≧90%. are used in electronic devices, electric or hybrid vehicles, industrial applications, and military applications such as drones. , aerospace applications, marine applications, and the like. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a scanning electron microscope photograph of the carbon material in Example 1 at 50,000 times magnification. [Diagram 2] FIG. 2 is a 0.1 C charge / discharge curve of the lithium selenium battery in Example 1. [Diagram 3] FIG. 3 is a 0.1 C charge / discharge curve of the lithium selenium battery in Comparative Example 2. [Figure 4] FIG. 4 is an optical image of the pouch-type cell battery of Example 1. [Diagram 5] FIG. 5 shows the 0.05C charge / discharge curves of the pouch-type cell battery of Example 1. [Figure 6] FIG. 6 is a flow diagram of a method for producing immobilized selenium. [Figure 7] FIG. 7 is a scanning electron microscope image of the carbon skeleton produced by the process of Example 9. [Figure 8] FIG. 8 is an X-ray diffractogram of the carbon skeleton produced by the process of Example 9. [Figure 9] FIG. 9 is a Raman spectrum of the carbon skeleton produced by the process of Example 9. [Figure 10A] FIG. 10A is a graph of the cumulative and incremental surface area of carbon skeletons produced by the process of Example 9. [Figure 10B] FIG. 10B is a graph of the cumulative and incremental pore volume of the carbon framework produced by the process of Example 9. [Figure 11A] FIG. 11A is a graph of the TGA analysis for immobilized selenium produced by the process of Example 10. [Figure 11B] FIG. 11B is a graph of a TGA analysis of a non-immobilized selenium sample produced by the process of Example 10 using Se-Super P carbon and Se graphite. [Figure 11C] FIG. 11C is a graph of the TGA analysis of non-immobilized selenium samples prepared using Se-SuperP carbon (FIG. 11B) at heating rates of 16° C. / min and 10° C. / min under flowing argon gas. [Figure 11D] FIG. 11D is a graph of the rate constants for non-immobilized selenium (Se-SuperP complex--solid line) and two different immobilized selenium samples (228-110 (dotted line) and 115-82-2 (dashed line)) produced by the process of Example 10. [Figure 12] FIG. 12 is a graph of the Raman spectrum of immobilized selenium produced by the process of Example 10. [Figure 13] FIG. 13 is a graph of the X-ray diffraction pattern of immobilized selenium produced by the process of Example 10. [Figure 14] FIG. 14 is an SEM image of immobilized selenium produced by the process of Example 10. [Figure 15] FIG. 15 is an exploded view of a coin cell battery including a cathode manufactured according to the process of Example 11 or Example 13. [Figure 16]FIG. 16 is a graph of cycle test results of a first lithium-selenium coin cell battery (0.1C) (FIG. 16A-left) and a second lithium-selenium coin cell battery (0.1C and then 1C) (FIG. 16A-right) of the type fabricated by the process of Example 12 and shown in FIG. [Figure 17] FIG. 17 is a graph of cycle testing at different cycle rates for a lithium-selenium coin cell battery of the type shown in FIG. 15 manufactured by the process of Example 12. [Figure 18] FIG. 18 is a graph of 0.1 C cycling test results for a lithium-sulfur-doped selenium coin cell battery of the type shown in FIG. 15 prepared according to Example 13, using a polymer separator. [Figure 19] FIG. 19 is a graph of 1C cycling test results for a lithium-sulfur-doped selenium coin cell battery of the type shown in FIG. 15 prepared according to Example 13, using a polymer separator. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The invention will be further described below with reference to specific examples. The test methods in the following examples are all conventional. All reagents and materials were commercially available. It is available from retail stores.
[0031] Example 1: (A) Preparation of selenium-carbon composite material After crushing and milling, an appropriate amount of potassium citrate was added and heated at 800°C for 5 min under an inert atmosphere. Baked for 2 hours, cooled to room temperature, washed with dilute hydrochloric acid to neutral pH, filtered and dried. Obtain a two-dimensional carbon nanomaterial (Figure 1). The two-dimensional carbon material was mixed in a mass ratio of 50:50. and selenium are weighed out, and then the mixture is stirred and mixed uniformly with the ethanol solution of selenium. After evaporation, the mixture is dried in a drying oven. The dried mixture is heated to 240 °C for 5 °C / The sample was heated for 10 minutes at 450°C and then soaked for 3 hours. The temperature was then increased at 5°C / min to 450°C. The mixture was soaked for 20 hours and then cooled to room temperature to obtain a selenium-carbon composite material.
[0032] (B) Preparation of selenium-carbon composite cathode (positive electrode) The selenium carbon composite prepared as above and carbon black Super-P (TIM CAL) and binder CMC / SBR (mass ratio 1:1) were mixed together with water, kneaded, and Through coating, drying and other procedures, a selenium carbon composite cathode is obtained.
[0033] (C) Assembly of a lithium-selenium battery The selenium-carbon composite cathode prepared as above, lithium foil as the anode, and selenium Celgard membrane as the parater and 1M LiPF6 in EC / DMC as the electrolyte. Therefore, the lithium selenium coin cell battery and the lithium selenium pouch cell battery (Figure 4 ) and assembled.
[0034] (D) Lithium-selenium battery testing Use the charging and discharging device to charge and discharge the lithium-selenium coin cell battery and the lithium selenium pouch battery. A constant current charge / discharge test is performed on the cell battery. The test voltage range is 1.0V and 3.0V. The test temperature is 25°C. The discharge specific capacity and the charge / discharge current levels are selected. The charge and discharge current is typically 0.1C or 0.05C. The charge and discharge curves of the lithium selenium coin are shown in Figure 2, and specific test results are shown in Table 1 below. The test results of the lithium selenium pouch-type cell battery are shown in Figure 5.
[0035] Example 2: The conditions were the same as in Example 1 except that the raw material carbonized for the 2D carbon was sodium citrate. Same as Example 1. The battery test results are summarized in Table 1 below.
[0036] Example 3: The conditions were the same except that the carbonized raw material for the 2D carbon was potassium gluconate. Same as Example 1. The battery test results are summarized in Table 1 below.
[0037] Example 4: The conditions were the same as in Example 1, except that the high-temperature carbonization temperature of the carbon material was 650°C. The battery test results are summarized in Table 1 below.
[0038] Example 5: The dried mixture was heated to 300°C at 5°C / min and soaked at this temperature for 3 hours. Except for the above, the conditions were the same as in Example 1. The results of the battery tests are summarized in Table 1 below.
[0039] Example 6: The dried mixture was heated to 240°C at 5°C / min and soaked at this temperature for 3 hours. The temperature was increased to 600°C and then soaked at this temperature for 20 hours. The conditions were the same as in Example 1. The battery test results are summarized in Table 1 below.
[0040] Example 7: Lithium-selenium batteries use lithiated graphite anodes instead of lithium anode sheets. The conditions were the same as in Example 1, except that the batteries were packed using the same PET bottles. The test results are shown in the table below. To summarize in 1.
[0041] Example 8: Lithium-selenium batteries use lithiated silicon carbon anodes instead of lithium anode sheets. The conditions were the same as in Example 1, except that the batteries were packed using a card. The test results are as follows: This is summarized in Table 1 below.
[0042] Comparative Example 1: The conditions were the same as in Example 1, except that polyacrylonitrile was used as the raw material. The battery test results are summarized in Table 1 below.
[0043] Comparative Example 2: Conditions except that a one-step chemical process is used to prepare the selenium and carbon complex. The heating time is the same as in Example 1. In this example, the dried selenium carbon mixture is heated to 500° C. at 5° C. / min. The temperature was raised to 100° C. and the mixture was soaked at this temperature for 23 hours to obtain a selenium-carbon composite material. The charge and discharge curves of the battery made from the selenium carbon composite material obtained are shown in Figure 3. The test results are summarized in Table 1 below.
[0044] [Table 1]
[0045] The method for producing the selenium-carbon composite material, the method for producing immobilized selenium, and The use of immobilized selenium in, for example, secondary batteries will be described.
[0046] Selenium is an element in the same group as oxygen and sulfur, i.e. group 6 of the periodic table of the elements. In terms of its sufficiently high electrical conductivity, it may be more advantageous than oxygen and sulfur. No. 2012 / 0225352 discloses a lithium-selenium di-electrolyte battery with good capacity and cycleability. However, it is known that some water-based secondary batteries and sodium-selenium secondary batteries can be manufactured using the same method. The equivalent polyselenide anion shuttles between the cathode and anode of such a cell, producing This provides additional electrochemical activity that needs to be substantially improved in use. Relevant literature in this field includes:
[0047] “Electrode Materials for Rechargeable Batteries”, Ali Aboulmrane and Khalil A mine, US Patent Application 2012 / 0225352, Sept. 6, 2012.
[0048] “Lithium-Selenium Secondary Batteries Having non-Flammable Electrolyte”, Hui He, Bor Z. Jang, Yanbo Wang, and Aruna Zhamu, US Patent Application 2015 / 0064575 , March 5, 2015.
[0049] “Electrolyte Solution and Sulfur-based or Selenium-based Batteries including t he Electrolyte Solution”, Fang Dai, Mei Cai, Qiangfeng Xiao, and Li Yang, US Pa tent Application 2016 / 0020491, Jan. 21, 2016.
[0050] “A New Class of Lithium and Sodium Rechargeable Batteries Based on Selenium an d Selenium-Sulfur as a Positive Electrode”, Ali Abouimrane, Damien Dambournet, Kerena W. Chapman, Peter J. Chupa, Wei Wang, and Khalil Amine, J. Am. Chem. Soc. 2012, 134, 4505-4508.
[0051] “A Free-Standing and Ultralong-life Lithium-Selenium Battery Cathode Enabled b y 3D Mesoporous Carbon / Graphene Hierachical Architecture”, Kai Han, Zhao Liu, J ingmei Shen, Yuyuan Lin, Fand Dai, and Hongqi Ye, Adv. Funct. Mater., 2015, 25, 455-463.
[0052] “Micro- and Mesoporous Carbide-Derived Carbon-Selenium Cathodes for High-Perfo rmance Lithium Selenium Batteries”, Jung Tai Lee, Hyea Kim, Marin Oschatz, Dong -Chan Lee, Feixiang Wu, Huan-Ting Lin, Bogdan Zdyrko, Wan Il Chao, Stefan Kaskel , and Gleb Yushin, Adv. Energy Mater. 2014, 1400981.
[0053] “High-Performance Lithium Selenium Battery with Se / Microporous Carbon Composit e Cathode and Carbonate-Based Electrolyte”, Chao Wu, Lixia Yuan, Zhen Li, Ziqi Yi, Rui Zeng, Yanrong Li, and Yunhui Huang, Sci. China Mater. 2015, 58, 91-97.
[0054] “Advanced Se-C Nanocomposites: a Bifunctional Electrode Material for both Li-S e and Li-ion Batteries”, Huan Ye, Ya-Xia Yin, Shuai-Feng Zhang, and Yu-Guo Guo, J. Mater. Chem. A., May 23, 2014.
[0055] “Lithium Iodide as a Promising Electrolyte Additive for Lithium-Sulfur Batteries es: Mechanisms of Performance Enhancement”, Feixiang Wu, Jung Tae Lee, Naoki Ni tta, Hyea Kim, Oleg Borodin, and Gleb Yushin, Adv. Mater. 2015, 27, 101-108.
[0056] “A Se / C Composite as Cathode Material for Rechargeable Lithium Batteries with Good Electrochemical Performance”, Lili Li, Yuyang Hou, Yaqiong Yang, Minxia Li , Xiaowei Wang, and Yuping Wu, RSC Adv., 2014, 4, 9086-9091.
[0057] “Elemental Selenium for Electrochemical Energy Storage”, Chun-Peng Yang, Ya-X ia Yin, and Yu-Guo Guo, J. Phys. Chem. Lett. 2015, 6, 256-266.
[0058] “Selenium@mesoporous Carbon Composite with Superior Lithium and Sodium Storage Capacity”, Chao Luo, Yunhua Xu, Yujie Zhu, Yihang Liu, Shiyou Zheng, Ying Liu, Alex Langrock, and Chunsheng Wang, ACSNANO, Vol. 7, No. 9, 8003-8010.
[0059] Also disclosed herein is immobilized selenium comprising selenium and carbon. The immobilized selenium is in elemental form. Selenium may include, but is not limited to, selenium in the form of sulfur or in a compound form. The immobilized selenium can be used in the cathode and anode of a battery. This allows for the localization of elemental selenium atoms that function properly electrochemically without shuttling between The immobilization of selenium occurs when an elemental selenium atom gains two electrons during the discharge process. In addition, the formation of selenide anions at the sites where selenium molecules / atoms are immobilized The selenide anion then gives up two electrons during the charging process to become the element Se. Therefore, immobilized selenium can be formed at a stoichiometric level. It can serve as an electrochemical activator for a secondary battery having a specific capacity of ≧95%, ≧ It can have a coulombic efficiency of 98% or even 100%, and is a significant improvement. This allows for a sustainable cycling capability to be realised.
[0060] In a battery made with immobilized selenium, elemental selenium atoms and selenide are separated during charging. Electrochemical behavior with anions is preferably a well-functioning process. 2 carbon The carbon skeleton with -carbon bonds is a G-band graphene that is inhibited by the D-band carbon. Delocalized electrons distributed throughout conjugated six-membered aromatic π bonds over a ring-like local network In the presence of an electric potential, such delocalized electrons result in almost no electrical resistance across the carbon backbone. The immobilization of selenium occurs with the S of the carbon skeleton. p 2 Carbon-carbon bonds can also be compressed, resulting in stronger carbon-carbon bonds and carbon bones. This may lead to improved electronic conductivity in the lattice network. The immobilization of selenium also leads to compaction of the selenium particles, which leads to chemical and physical interactions between selenium and selenium. This can result in stronger interactions and improve electrical conductivity between immobilized selenium particles. When both the carbon-carbon bond and the Se-Se bond are strengthened by the immobilization of In addition to the presence of stabilizing selenium moieties that can bind, compression also enhances carbon-selenium interactions. The selenium moiety is stabilized by the carbon skeleton, which effectively fixes the selenium moiety. Therefore, it can act as an interfacial layer between the carbon skeleton and the immobilized selenium. In secondary batteries, electrons can flow with minimal electrical resistance, and the electrochemical charging / discharging process is This, in turn, allows secondary batteries to function efficiently at near stoichiometric specific capacities. The battery’s electrochemical performance can be maintained at a low level while still maintaining almost It has cycle characteristics at all practical rates.
[0061] The carbon skeleton may be porous or doped with other components. The pore size distribution may range from sub-angstroms to several microns; The pore size distribution is determined by using nitrogen, argon, CO2, or other adsorbents as the probe molecules. The range may be up to the pore size that the pore size distribution device can characterize by performing the above-mentioned steps. The pores of the carbon skeleton may include a pore size distribution having a peak in at least one of the following ranges: It can be between sub-angstroms and 1000 angstroms or 1 angstrom. Between 1 angstrom and 100 angstroms, or between 1 angstrom and 50 angstroms between 1 Angstrom and 30 Angstroms, and / or The spacing between the carbon skeleton and the lattice is between 1 and 20 Å. The pores have a pore size distribution having more than one peak within the range described above. Immobilized selenium is advantageous in carbon skeletons with small pore sizes, where the most The small electrical resistance allows electrons to be transferred and collected quickly, making selenium electrochemically more efficient in secondary batteries. Smaller pore sizes also provide more carbon skeleton surface area, where The first portion of selenium can form a first interface layer for the second portion of selenium immobilization. In the carbon skeleton, a predetermined proportion of medium-sized pores and a predetermined proportion of large-sized pores are present. The presence of the pores allows for efficient transport of the solvent lithium ions from the bulk solvent medium into the small pore regions. In this pore region, the lithium ions can be transported by the cooperating solvent molecules. It is possible that the cations lose their charge and are transported in the solid phase of lithium selenide.
[0062] The pore volume of the carbon skeleton can be as low as 0.01 mL / g and as high as 5 mL / g. or between 0.01 mL / g and 3 mL / g, or 0.03 mL / g and 2.5 mL / g, or between 0.05 mL / g and 2.0 mL / g. Less than 100 angstroms, or less than 50 angstroms, or less than 30 angstroms The pore volume with pore diameters less than 20 Å is considered to be the volume of nitrogen, CO2 , argon, and other probe gas molecules can be used to measure BET instruments. greater than 30%, or greater than 40%, or greater than 50% of the total pore volume; It may be greater than 60%, greater than 70%, or greater than 80%. The BET surface area of the carbon is 400m 2 / g or more than 500m 2 / g It may be larger than 600m 2 / g or more, or 700m 2 / g or more It is okay if it is less than 800m 2 / g or more, or 900m 2 / g or more or 1000m 2 / g.
[0063] The carbon may be substantially amorphous or may have a d-spacing of about 5 Angstroms. It may have the characteristic of a very broad peak with a center.
[0064] Carbon has Raman peak shifts characterized by D-band and G-band, Sp 2 It may contain a carbon-carbon bond. In one example, the carbon 2 Carbon-carbon bonds are In ktr, it is about 296±50 cm -1 FWHM of 1364±100cm -1 of The D-band at the center is approximately 96±50cm -1 FWHM of 1589±100c m -1 The area of the D-band relative to the G-band is The ratio may range from 0.01 to 100, or from 0.1 to 50, or 0. It may range from 2 to 20.
[0065] The carbon may be in any form, i.e., platelet, spherical, fibrous, needle-like, tubular, irregular, etc. In the form of a solid particle, an interconnected form, an aggregated form, a discrete form, or any solid particle, The shape may be platelet-like, fibrous, needle-like, tubular, or other shapes having a predetermined aspect ratio. Certain morphologies may be advantageous for achieving good interparticle contact, which may result in: This can result in better electrical conductivity and improve the performance of the secondary battery.
[0066] Carbon can range from 1 nanometer to several millimeters, or from a few nanometers to 1000 having a median particle size of submicron or from 20 nm to 100 microns; It may be of any particle size.
[0067] The nature of the carbon skeleton can affect selenium immobilization, and the surface of the carbon skeleton and the selenium The interaction between the carbon skeleton and the silicon particles may affect the performance of the secondary battery. Sp 2 The arrangement of carbon can help achieve Se immobilization. Sp from the septum 2 Carbon may be preferred, as described in Example 9 herein. The carbon skeleton is smaller than 20 Å and can be quantified by the NLDFT surface area method. The surface area from the hole is ≥ 500m 2 / g, ≥ 600m 2 / g, ≥700m 2 / g, ≧800 m 2 / g, ≥900m 2 / g, or ≥ 1,000m 2 / g. 20 oz. The surface area from the carbon skeleton pores between 1000 and 1000 Å is approximately 100% of the total surface area of the carbon skeleton. 20% or less, 15% or less, 10% or less, 5% or less, 3% or less, 2% or less of the surface area; It may be less than 1%.
[0068] Immobilized selenium is evaporated at a higher temperature than elemental selenium, see the definition of selenium evaporation below. The elemental selenium in the Se-Super P complex is 48 At a temperature of 0 °C, elemental selenium in the Se / graphite composite loses 50% of its mass and at a temperature of 471 °C At temperatures above 480°C, immobilized selenium loses up to 50% of its mass. For example, ≧490°C, ≧500°C, ≧510°C, ≧520°C, ≧530°C, ≧5 40°C, ≥550°C, ≥560°C, ≥570°C, or ≥580°C or higher At high temperatures, it loses 50% of its mass. In order to escape from the immobilized selenium and desorb into the gas phase, the selenium in the immobilized selenium must be ≥ 9.5 kJ / mol , ≧9.7 kJ / mol, ≧9.9 kJ / mol, ≧10.1 kJ / mol, ≧10.3 kJ / mol mol, or may require kinetic energy of ≥ 10.5 kJ / mol or more. In one example, the final portion of the immobilized selenium that vaporizes is released from the carbon skeleton. To do this, a kinetic energy of ≥ 11,635 Joules / mole (≥ 660°C) is required. This may be important for selenium immobilization, and the carbon skeleton and immobilized selenium molecule It can act as an interface material between the majority of the That portion of selenium that requires 1 / mol of kinetic energy is called interfacial selenium. The amount of interfacial selenium in selenium oxide is ≥ 1.5%, ≥ 2.0%, and ≥ 2. It may be 5% or 3.0%.
[0069] Immobilized selenium has the following problems to be overcome in order for selenium to be released from the immobilized Se-C complex system: Selenium with an activation energy higher than that of (non-immobilized) selenium The activation energy of non-immobilized selenium (Se-Super P complex system) is A It was determined to be about 92 kJ / mol according to STM method E1641-16. The activation energy of selenium in immobilized selenium containing carbon is ≥ 95 kJ / mol and ≥ 98 kJ / mol. kJ / mol, ≧101 kJ / mol, ≧104 kJ / mol, ≧107 kJ / mol, or ≧1 The activation energy of selenium in immobilized selenium containing selenium and carbon is 10 kJ / mol. The activation energy of selenium in the Se-Super P complex is ≥ 3% and ≥ 6%. %, ≥ 9%, ≥ 12%, ≥ 15%, or ≥ 18% greater. Immobilized selenium is The reason is that selenium is fixed in the Se-C complex. The selenium is probably most efficiently transported between the cathode and anode by the ion exchange. By miniaturizing (or eliminating) the selenium-containing battery, the cycle performance of the battery containing the immobilized selenium becomes more stable. This is because his academic performance improved.
[0070] Typically 255 ± 25 cm -1 , or 255±15cm -1 , or 255±10cm -1 The immobilized selenium has a Raman peak at The Raman relative peak intensity is calculated based on the D-band peak of the carbon Raman spectrum. of the area of the workpiece, 255 cm -1 It is defined as the area of the Raman peak at Carbon has Raman relative peak intensities of ≥0.1%, ≥0.5%, ≥1%, ≥3%, and ≥5%. The immobilized selenium may contain selenium that is ≧5% selenium, ≧10% selenium, ≧2 0% Selenium, ≥30% Selenium, ≥40% Selenium, ≥50% Selenium, ≥60% Selenium It may contain ≧70% selenium.
[0071] The immobilized selenium may include selenium having a red shift from the Raman peak of pure selenium. The red shift is due to the difference between the Raman peak position of immobilized selenium and that of pure selenium. , is defined by the positive difference between the ions. Pure selenium is typically around 235 cm -1 Llama The immobilized selenium has a peak of ≥4 cm. -1 , ≧6cm -1 , ≧8cm -1 , ≧1 0cm -1 , ≧12cm -1 , ≧14cm -1 , or ≧16cm -1 Raman peaks up to The red shift in the Raman peak can be calculated by adding selenium. This suggests that there is compression of the selenium particles.
[0072] The immobilized selenium may include carbon that may be under compression. Under compression, electrons are It can flow with a small resistance, which means that in secondary batteries, electricity Facilitates rapid electron transfer from selenium anions to selenium involved in chemical processes. Selenium-containing carbon skeletons, Sp 2 D- in Raman spectra related to carbon-carbon bonds Bands and / or G-bands ≥ 1 cm -1 , ≧2cm -1 , ≥ 3cm -1 , ≥ 4cm -1 , or ≧5cm -1 may exhibit a red shift of up to 1000 nm.
[0073] Immobilized selenium includes selenium that may have a higher collision frequency than non-immobilized selenium. Such a high collision frequency may be due to selenium in the immobilized Se-C system under compression. The collision frequency of selenium in non-immobilized selenium is based on the ATSM method E1641-16. Therefore, about 2.27 x 10 5 The results showed that immobilized selenium containing selenium and carbon The collision frequency of selenium in is ≧2.5×10 5 , ≧3.0×10 5 , ≥ 3.5 × 10 5 , ≧4.0×10 5 , ≧4.5×10 5 , ≧5.0×10 5 , ≧5.5×10 5 , ≧6.0 ×10 5 , or ≥ 8.0 × 10 5 The immobilized selenium is the equivalent of the non-immobilized selenium in the Se-C complex. The collision frequency of selenium is ≥10%, ≥30%, ≥50%, ≥80%, ≥100%, and ≥1 30%, ≥150%, ≥180%, or ≥200% higher collision frequency. This may lead to better electronic conductivity in the immobilized selenium system. This is due to more collisions between selenium species. It is expected that the nuclei will also have a higher collision frequency against the walls of the nuclei (e.g., the carbon skeleton). This allows for better delivery or collection of electrons from the carbon backbone during electrochemical cycling. This can result in more cycles and a significantly higher C, which is highly desirable. Improved cycling performance, such as cycling at high rates (including immobilized selenium) A battery can be provided.
[0074] Immobilized selenium contains selenium that is less prone to leaving its host material (carbon). The kinetic rate constants of non-fixed / conventional selenium are ≦1 / 5, ≦1 / 10, ≦1 / 50. , ≦1 / 100, ≦1 / 500, or ≦1 / 1000. In the present study, immobilized selenium has a lower tendency to leave its host material (carbon). Including, ≦1×10 -10 , ≦5×10 -11 , ≦1×10 -11 , ≦5×10 -12 ,also is ≦5×10 -13 (50°C).
[0075] The immobilized selenium may be amorphous as determined by X-ray diffraction measurements. The diffraction peak with a d-spacing of about 5.2 angstroms is relatively small. or weaker than the diffraction peak of the carbon skeleton, for example, 10% weaker, 20% weaker, 30% weaker Weak, or 40% weaker.
[0076] Immobilized selenium is prepared by physically mixing carbon and selenium, and then melting and homogenizing the selenium molecules. By modifying (or mixing or blending) the selenium to achieve immobilization of the selenium, Physical mixing can be performed using a ball mill (dry and wet), a mortar and pestle (dry or Wet mixing, jet mill, horizontal mill, grinding mill, high shear mixing in slurry, This can be done by conventional slurry mixing using a grinder. The mixture of selenium and carbon is heated at a temperature equal to or higher than the melting point of selenium and lower than the melting point of carbon. It can be heated at 35° C. or under an inert gas environment such as, but not limited to, argon, helium, or nitrogen. The heating environment may include air or a reaction environment. Fixation of selenium The conversion can be achieved by impregnating the carbon with dissolved selenium, followed by evaporation of the solvent. Solvents for dissolving selenium include alcohols, ethers, esters, ketones, and carbon dioxide. Hydrogen, halogenated hydrocarbons, nitrogen-containing compounds, phosphorus-containing compounds, sulfur-containing compounds, water, etc. may include:
[0077] Immobilized selenium is produced by dissolving large amounts of selenium in the presence of carbon, followed by the subsequent decomposition of the unimmobilized selenium. This can be achieved by removing excess selenium.
[0078] A fixed selenium system or body is defined as the total amount of selenium in the system or body. of ≥ 30%, ≥ 40%, ≥ 50%, ≥ 60%, ≥ 70%, ≥ 80%, or ≥ 90% of the amount The non-immobilized selenium may be vaporized at a lower temperature than the immobilized selenium. possible.
[0079] The immobilized selenium system or body may be any of the selenium elements of the periodic table, such as sulfur and / or tellurium. Immobilized selenium doped with one or more additional elements / other elements from group 6 of The dopant concentration is preferably 100 mass p of the mass of the immobilized selenium system or the immobilized selenium body. It may range from as low as pm to as high as 85% by weight.
[0080] An example of the process for producing immobilized selenium is shown in Figure 6. In this process, selenium and The mixture is mixed with carbon under dry or wet conditions (S1). The mixture is dried as necessary. After powdering (S2), the dry powder can be pelletized (S3) if desired. As a result of step S1 and, optionally, steps S2 and S3, starting material for step S4 In step S4, selenium is dissolved in the carbon skeleton. The molten selenium can be dried, thereby producing immobilized selenium in step S5. The preparation and characterization of immobilized selenium is described later in this specification in connection with Example 10. It is stated that:
[0081] The immobilized selenium can be used as a cathode material for secondary batteries. Alternatively, the immobilized selenium may be dispersed in a liquid medium, such as, but not limited to, water or an organic solvent. The cathode containing immobilized selenium is made of a binder and, optionally, a second binder and, optionally, The binder may optionally include a conductivity promoter and a current collector. The organic binder may be a natural product, such as CMC, or a non-natural product, such as S The conductive promoter may be a compound such as BR rubber latex. Carbon such as laphene, carbon nanotubes, carbon nanosheets, and carbon black The current collector may be, for example, an aluminum foil, a copper foil, a carbon foil, a carbon fiber, or The cathode may be a metal foil or other metal foil. The cathode is a slurry containing immobilized selenium (or a mixture of slurries). The coating is applied to the current collector, followed by a typical drying process (air drying, oven drying, vacuum oven drying, etc.). The immobilized selenium slurry or the multiple-type slurry can be produced by the following methods: High shear mixer, regular mixer, planetary mixer, double planetary mixer The immobilized selenium can be produced by a furnace, a ball mill, a vertical attritor, a horizontal mill, etc. The cathode may be pressed prior to use in a battery assembly, or It may also be roller milled (or calendered).
[0082] The secondary battery containing immobilized selenium comprises a cathode containing immobilized selenium, an anode, and a separator. The anode may include a lithium, sodium, silicon, or black alloy. Lead, magnesium, tin, and / or group IA, I in the periodic table of the elements Any suitable and / or desirable element or combination of elements from groups IA, IIIA, etc. The separator may be an organic separator, an inorganic separator, or a solid An electrolyte separator may be included. Organic separators include, for example, polyethylene, poly Polypropylene, polyester, halogenated polymers, polyethers, polyketones, etc. The inorganic separator may include glass fiber or quartz fiber, a solid electrolyte, etc. The electrolyte may include a lithium salt, a sodium salt, or other salt, a periphery, The organic solvent may include a salt of Group IA of the Periodic Table, a salt of Group IIA of the Periodic Table, and an organic solvent. The solvents are organic carbonate compounds, ethers, alcohols, esters, hydrocarbons, halogens, etc. These may include fluorocarbons, lithium-containing solvents, and the like.
[0083] Electronics, electric or hybrid vehicles, industrial applications, Immobilized selenium for military, aerospace, and marine applications, such as drones. A secondary battery including the above-mentioned can be used.
[0084] Secondary batteries containing immobilized selenium have a selenium activity of 400mAh / g or more and 450 mAh / g or more, 500mAh / g or more, 550mAh / g or more, or 600mAh / g The secondary battery containing immobilized selenium can have a specific capacity of 7000 or more cycles. Electrochemical cycles over 5 cycles, over 100 cycles, and over 200 cycles can be received.
[0085] A secondary battery containing immobilized selenium was charged at 0.1C, 0.2C, 0.5C, 1C, 1.5C, and 2 Charge at C, 3C, 4C, 5C, 6C, 7C, 8C, 9C, 10C or faster More than 30 charge / discharge cycles at a wide range of high C rates (e.g., 0 5 cycles at .1C, 5 cycles at 0.2C, 5 cycles at 0.5C, 5 cycles at 1C 5 cycles at 2C, 5 cycles at 5C, and 5 cycles at 10C) were performed, followed by immobilization. Secondary batteries containing ethylene are discharged at a cycle rate of 0.1C and have a specific capacity of >30% on the second discharge. , >40%, >50%, >60%, >70%, >80% of the battery capacity can be maintained. Cut.
[0086] Below are some examples to illustrate the concept of the present invention. The examples should not be construed in a limiting sense.
[0087] Characterization Method Tescan Vega scanning electron microscope equipped with an energy dispersive X-ray (EDX) detector Scanning electron microscopy (SEM) images were collected under a microscope.
[0088] The Renishaw inVia Raman spectrometer (confocal) Laser Raman spectroscopy has been used to characterize carbon and diamond. It is widely used and has a good reputation, and is used in many applications such as carbon (e.g. diamond, graphite, buckybarium, etc.). It provides an easily distinguishable characterization of the various forms (allotropes) of fluorine (e.g., fluorine). By combining with PL (photoluminescence) techniques, it is possible to determine the purity of the phase, the size and orientation of the crystals, Diamond properties such as defect levels and structure, impurity types and concentrations, stress and strain, etc. This method provides a non-destructive way to investigate various properties. -1 To The width of the first diamond Raman peak (full width at half maximum, FWHM) and the doped peak and graphite peak (1350cm -1 D-band at 1600 cm -1 G- The Raman intensity ratio between the 1 and 2 bands is a direct indicator of the quality of diamond and other carbon materials. In addition, the stress and strain levels in diamond or other carbon particles and films can be determined by: It can be estimated from the Raman peak shift of diamond. Ndraman peak shift speed is about 3.2 cm -1 / GPa, which is low under tensile stress. It has been reported that the peak shifts to higher wavenumbers under compressive stress. The Raman spectra discussed herein were obtained using a 514 nm excitation laser. , collected using a Renishaw inVia Raman spectrometer. For more information about using Raman spectroscopy to characterize Zaitsev, Optical Properties of Diamond, 2001, Springer, and (2) S. Prawer, R. In reference to J. Nemanich, Phil. Trans. R. Soc. Lond. A (2004) 362, 2537-2565. is also possible.
[0089] Data on the BET surface area and pore size distribution of the carbon samples were obtained using the S Using 3Flex (Mircomeritics) equipped with mart VacPrep The samples were usually measured by CO2 and N2 absorption. Before the determination, the samples were degassed in a Smart Vac-Prep at 250 °C for 2 h under vacuum. Nitrogen absorption is used to measure the BET surface area. Nitrogen absorption data and CO2 absorption data The pore size distribution of the carbon sample was calculated by combining the above. For more information on combining both N2 and CO2 absorption data for gas analysis of microporous carbon using 2D-NLDFT heterogeneous surface model a nd combined adsorption data of N2and CO2”, Jacek Jagiello, Conchi Ania, Jose B Parra, and Cameron Cook, Carbon 91, 2015, pages 330-337.
[0090] Thermogravimetric analysis (TGA) and TGA-differential scanning calorimetry (DSC) were performed on the immobilized selenium samples and control samples. The data related to the amount of heat and the amount of heat measured (DSC) are collected by Netzsch Thermal Analyze The temperature was measured at heating rates of 16°C / min, 10°C / min, 5°C / min, 2°C / min, and 1°C / min. TGA analysis was performed at 100° C. and other heating rates under an argon flow rate of ∼200 mL / min. For consistency purposes, typical amounts of immobilized selenium samples used for TGA analysis are was approximately 20 mg.
[0091] The activation energy and collision frequency of immobilized and non-immobilized selenium were measured according to the ASTM method. The concentration was measured by TGA according to the procedure described in E1641-16.
[0092] For various carbons, Se-carbon samples, and immobilized selenium, Philip Diff X-ray diffraction results were collected on a ractometer.
[0093] Secondary batteries containing immobilized selenium were tested using the Lanhe CT2001A battery cycle tester. The battery cycle performance of the battery was tested. The amount of selenium contained in the immobilized selenium and the cycle rate Depending on the temperature (0.1C, 0.5C, 1C, 2C, 3C, 4C, 5C, 10C, etc.), The charge and discharge currents of the secondary battery containing selenium chloride were measured.
[0094] Example 9: Synthesis and characterization of carbon scaffolds To form the first residue, a 260 g charge of potassium citrate was placed in a crucible and heated. The tube was placed in a quartz tube in a tubular furnace. A flow of argon gas was passed through the furnace and the furnace was heated to room temperature (~20-22 °C). The temperature was increased from 100° C. to 600° C. at 5° C. / min. The furnace was held at this temperature for 60 minutes, after which the furnace was shut down. After the furnace was cooled, the crucible was emptied of its charge and 174.10 g of treated residue was recovered. To form the second and third treated residues, the same steps as described for the first residue are repeated, Separate charges of 420 g and 974 g potassium citrate were repeated. The second and third treatment residues were 282.83 g and 651.93 g, respectively.
[0095] The 1108.9 g from the residues of these three treatments was combined and placed in a crucible. The tube was placed in a quartz tube in a furnace and a stream of argon gas was allowed to flow through the furnace. The furnace was heated to 800 °C at 5 °C / min. The furnace was kept at 800°C for 1 hour. After the furnace was cooled, the crucible was removed from the quartz tube. Afterwards, 1,085.74 g of the first final residue was recovered.
[0096] 120 g of sucrose were introduced into the furnace according to the same procedure (800° C.) as described in this example. The charge of potash residue produced about 77 g of second final residue (800° C.).
[0097] The first and second final residues were combined to produce a third final residue of approximately 1,163 g. was brought about.
[0098] The third final residue (1,163 g) was mixed with 400 mL of water to prepare a slurry, which was then divided into four The pH of each slurry was measured to be greater than 13. A concentrated hydrochloric acid solution was then added to each beaker, accompanied by a vigorous evolution of carbon dioxide, until approximately Precipitation occurred at a pH below 5. More hydrochloric acid solution was added to obtain a pH of about 1.9. The slurry was then filtered and the washed filter cake was placed in an oven at 120° C. for about 12 hours. After drying, followed by vacuum drying at 120°C for 24 hours, four carbon skeleton samples were obtained. The weight was approximately 61.07g.
[0099] These carbon skeleton samples were characterized by SEM, XRD, Raman, and BET / pore size distribution. The SEM image of the carbon skeleton of 1 is shown in FIG. The surface morphology of a typical carbon skeleton particle produced by the method described above has a sheet-like morphology, and the sheet edges are The sections are interconnected with a sample thickness between 500 nm and 100 nm, and the sample width (or length) is , between 0.5 μm and 2 μm. Therefore, the aspect ratio (sample width to sample thickness) (or sheet length) is ≧1, for example, aspect ratio ≧5 or larger, or the aspect ratio is ≧10.
[0100] The X-ray diffraction pattern of the carbon skeleton of 1, shown in FIG. 8, indicates that the carbon skeleton is substantially amorphous in phase. However, this is due to a broad diffraction peak centered around 2θ of about 17°. The graph shows a d-spacing of about 5.21 Angstroms.
[0101] The results of Raman scattering spectroscopy for the carbon skeleton of 1 are shown in FIG. 9, which shows that 6cm -1 and 96cm -1 The FWHM is about 1365 cm -1 D-band ( Curve 1) and about 1589 cm -1 G-band (curve 2) and Sp 2 Carbon Both the D-band and G-band show a mixture of Gaussian and Lorentzian distributions. The D-band has a Gaussian distribution of about 33% and the G-band has a Gaussian distribution of about 61%. The ratio of the area of the D-band to the area of the G-band is about 3.5.
[0102] Upon nitrogen adsorption, the BET surface area of the carbon skeleton of 1 is 1,205 m 2 / g The incremental pore surface area versus pore width was plotted in Figure 10A using the NLDFT method. The cumulative pore surface area is 1,515 m 2 / g. BET surface area and NL The discrepancy between the NLDFT surface area and the NLDFT distribution was due to the use of both nitrogen and CO2 adsorption data. This may be due to the fact that the calculation is done with the nitrogen molecule. It can enter pores smaller than the pores in which it can be formed. It has a peak at 3.48 angstroms. The NLDFT surface area in the pores is 443 m 2 / g, and 8 at 5.33 angstroms. 59m 2 / g, and 11.86 Å (up to 20 Å) 85m 2 / g. The total for pores less than 20 angstroms is 1,502 m 2 / g, while N from pores between 20 Å and 1000 Å The LDFT surface area is only 7.5m 2 / g, and from pores of 20 Å or more The surface area is only about 0.5% of the total surface area.
[0103] The pore size distribution of the carbon skeleton samples was determined by nitrogen and CO2 absorption. The pore size distribution shown in Figure 10B was obtained by combining the absorption results from the pore volume and CO2 absorption. The relationship between volume (mL / g) and pore width (Angstroms) is 3.66 Angstroms. , 5.33 Å, and 11.86 Å. Cumulative pore volume (mL / g) vs. pore width (Angstroms) The relationship is that there is a pore volume of approximately 0.080 mL / g under the 3.66 angstrom peak. There is a pore volume of approximately 0.240 mL / g under the 5.33 Å peak, and the pore volume is 11.86 This indicates that there is a pore size of about 0.108 mL / g under the 20 Å peak. The pore size is 0.43 mL / g, and the pore size is 20 Å and 100 Å. The pore size is 0.042 mL / g, and the pore size is up to 1000 Å. The total pore size is 0.572 mL / g.
[0104] Example 10: Preparation and characterization of immobilized selenium In a pair of agate mortars and pestle, add 0.1206 g of selenium (to represent the bulk properties of selenium). 0.1206 g of the carbon skeleton prepared according to Example 9 was placed in the same agate mortar and pestle. The mixture of selenium and carbon skeleton is manually ground for about 30 minutes to obtain a powder of selenium and carbon skeleton. The crushed mixture is transferred to a stainless steel die (diameter 10 mm). The mixture in the die is concentrated to about 10 mm. The mixture is then compressed at a pressure of 100 MPa to form a pellet. The pellets are placed in a sealed container under a high temperature and the sealed container containing the pellets is placed in an oven. The oven containing the sealed container containing the selenium is heated to 240°C (above the melting point of selenium), for example, 12 However, the selenium and carbon may react partially or completely to form the The time and the selenium can be used to form immobilized selenium having some or all of the characteristics described. The use of any combination of temperatures above the melting point of the propylene is contemplated. After returning to room temperature, the pellets are removed from the container. The removed pellets are It is fixed selenium at 0.
[0105] The immobilized selenium of this Example 10 was characterized by TGA-DSC and TGA. The TGA-DSC analysis results for immobilized selenium were obtained with argon gas at 200 mL / min. The temperature was raised at a rate of 10°C / min. The temperature was measured at a temperature close to the melting point of selenium (approximately 230°C). There is no possible endothermic DSC peak, which indicates that the immobilized selenium of this Example 10 is Unlike the bulk form of selenium molecules / atoms, which should have a melting point at about 230°C, there should be a thermal peak. It is shown that...
[0106] The temperature at which selenium molecules begin to leave the TGA-DSC sample crucible (graphite or ceramic) When the heating temperature is reached, the TGA-DSC data may not be reliable. The results of the study revealed that gas-phase selenium molecules (from the sample crucible) were They enter the carrier gas stream and react with the platinum sample holder of the TGA-DSC, SC is believed to distort the thermochemical behavior. The selenium molecule reacts with the platinum sample, resulting in a lower mass loss in this temperature range. The selenium-platinum complex in the selenium-platinum complex then dissolves into a gas phase when the heating temperature reaches a point above 800 °C. The complete release of selenium can occur at 1000°C. Most of the immobilized selenium samples from Example 10 were used. A new sample of immobilized selenium (~16 g) was prepared using the same method as described above.
[0107] TG with a ceramic sample holder to cover very small thermocouples used in TGA analysis The thermochemical behavior of this new immobilized selenium sample was studied by A analysis. The TGA analysis results of the stabilized selenium sample are shown in FIG. 11A. 1B) and in the same process as the production of immobilized selenium in Example 10. Selenium-carbon complexes (50-50, Se-Super P carbon complex and Se-black The Super P is made of lithium-ion batteries (pulverized graphite) and It is a commercial grade of carbon black that is widely used in the battery industry. It was produced by crushing oco 2020 graphite. The TGA analysis data is also as follows: These are summarized in Table 2.
[0108] [Table 2]
[0109] Immobilized selenium may have an initial mass loss temperature beginning at about 400° C. In contrast, For the Se-Super P carbon composite and the Se-graphite carbon composite, the reaction started at approximately 340°C. The intermediate mass loss temperature of the immobilized selenium is about 595° C. In contrast, the Se-Super P composite material is at 480℃, and the Se-graphite composite material is at 480℃. In the case of the Se-Super P composite and the Se-graphite composite, The main mass loss was completed at about 544 °C for the selenium and 660 °C for the immobilized selenium. The e-Super P carbon composite and the Se-graphite carbon composite were heated between 560℃ and 780℃. The immobilized selenium showed a mass loss of less than 0.6% at 660°C. The mass loss from 1000°C to 1000°C is about 2.5%. These results suggest that Non-immobilized selenium (Se-Super P carbon composite and Se-graphite composite) is ≧560 While less than 1.2% of the total selenium is available to be released from the complex at temperatures of 30°C, the immobilized selenium has about 5.0% of the total selenium that can be released from the carbon skeleton at temperatures of ≥ 660°C The following details are provided to give examples that provide insight into the thermochemical behavior. However, these details should not be construed in a limiting sense.
[0110] As an example of thermochemical behavior, the data of intermediate mass loss temperature in TGA is used. When the temperature increased, the selenium content in the Se-Super P composite and the Se-graphite composite increased. The kinetic energy of the molecules escapes from the intermolecular interactions of the selenium molecules, and the selenium moves from the liquid phase The selenium molecule then rises to a level where it has enough energy to break away. Kinetic energy = 3RT / 2, where R is the gas constant and T is the temperature in Kelvin. .
[0111] The average kinetic energy of the selenium molecules in the Se-Super P complex is When a selenium molecule leaves a mixture of P complexes, it has a mass of 9,391 Joules / mole. However, as selenium leaves the carbon skeleton and moves into gas-phase selenium molecules, In fact, immobilized selenium has an average kinetic energy of about 10,825 Joules / mole. The selenium in the immobilized selenium is in the atomic state, molecular state, or In any of the arbitrary states, selenium and carbon can be separated by intermolecular interactions with selenium. It is believed that the nucleus can chemically interact with the skeleton. The final part of selenium that leaves the carbon skeleton is 11,635 joules / mole to 15, The average kinetic energy ranges from 876 Joules / mole or more. This is because immobilized selenium This suggests that the selenium in the selenium-carbon composite is more stable than that in conventional selenium-carbon composites. The stabilized selenium in the immobilized selenium of Example 10 may be in an atomic state, a molecular state, or any other state. The charge and discharge cycle of a secondary battery composed of immobilized selenium is called In one example, the ability of the cations to remain inside the carbon skeleton during electrochemical processes , the last portion of selenium requires ≥ 11,635 Joules / mol to leave the carbon skeleton. (≧660°C) of kinetic energy, which is important for the immobilization of selenium. It is possible that the selenium-immobilized selenium complex may function as an interface material between the carbon skeleton and the bulk of the immobilized selenium molecules. The portion of interfacial selenium in the immobilized selenium is ≥ 1.5% of the total immobilized selenium. %, ≧2.0%, ≧2.5%, or 3.0%.
[0112] FIG. 11A shows the intermediate mass loss point of the incorporated selenium at a heating rate of 16° C. / min. Also shown is a TGA study of immobilized selenium, which has a temperature of 628° C. at 100° C. As shown in FIG. In the case of the Se-Super P composite, the intermediate Se content was increased at a heating rate of 16°C / min. The temperature at mass loss is 495°C. Various heating rates (e.g., 16°C / min, 10°C / min) min, 5°C / min, 2.5°C / min, and 1°C / min) were used to measure the temperature in accordance with ASTM E1641-16 Activation energies and collision frequencies were measured using known methods such as E2958-14 and E2958-14. The 15% mass loss temperature for various heating rates is shown in Table 3 below. show.
[0113] [Table 3]
[0114] The activation energy of selenium (non-immobilized or conventional) in the Se-Super P complex is , 2.27×10 5 It was measured to be 92.3 kJ / mol at a collision frequency of 1.0 kJ / mol. The activation energy of selenium in selenium chloride (228-110 above) is also 12.4 × 1 0 5 The collision frequency was measured to be 120.7 kJ / mol. Same as Example 10 Another sample of immobilized selenium produced by the process (155-82-2 above) also showed a 120 .0 kJ / mol activation energy and 18.3 x 10 5 The collision frequency is was measured.
[0115] The kinetic rate constant of selenium is calculated using the Arrhenius equation.
number
[0116] Referring to FIG. 11D, using the activation energies and collision frequencies measured above, various Kinetic rate constants were calculated using the Arrhenius equation at various velocities. Se-Super P complex (solid line) is immobilized selenium (228-110 (point The results show that 115-82-2 (dashed line) and 115-82-2 (solid line) have much higher rate constants than 115-82-2 (solid line). For example, it is about four orders of magnitude larger at 35°C and about three orders of magnitude larger at 100°C. The immobilized selenium was 7.26 × 10 14 (155-82-2) and 3.78×10 14 The rate constant of the reaction is (228-110), whereas that of non-immobilized selenium (Super P) is (228-110). The degree constant is 2.668 x 10 -10 Selenium, which has a lower kinetic rate constant, is The carbon is less likely to leave the support material, which results in better battery cycling performance. It can be done.
[0117] Figure 12 shows the 1368 cm -1 D-band and 1596 cm -1 G-band radio The spectrum of immobilized selenium with Mann peaks is shown, and the area of the D-band relative to the area of the G-band is shown. The area ratio of the bands is 2.8. Compared with the Raman spectrum of the carbon skeleton shown in Figure 9, Selenium immobilization shifts both Raman peaks to higher wavenumbers, while the D-band Approximately 3cm -1 red shift of about 7 cm for the D-band -1 There is a red shift of This is the Sp 2 This suggests that the bond strength of carbon is strengthened, and D - Band length: approx. 4cm -1 for the G-band, there is a red shift of about 8 cm. - 1 At the same time, the ratio of the D-band area to the G-band area also changes by about 3.4 to 2.8, the D-band becomes relatively weak, or the G-band becomes relatively It has been suggested that the G-band is stronger than the G-band. A stronger G-band may be desirable. The carbon skeleton is a carbon species that can conduct electrons more easily when used in secondary batteries. This is because the carbon species that are most favorable for electrochemical performance may be related to the bulk Selenium or pure selenium typically has a molecular weight of about 235 cm -1 A sharp Raman peak shift was observed In the case of immobilized selenium, the Raman spectrum in Figure 12 shows a peak at about 257 cm -1 Wide range of Raman A peak (12.7% of the G-band area) was observed at approximately 500 cm -1 New wide hump (hump, shoulder) (3.0% of the G-band area). Selenium immobilization is due to the carbon skeleton and selenium The Raman characteristics of both the fluorescein and the fluorine-containing fluorescein were changed, and all the Raman peaks were shifted to higher wavenumbers. This is thought to result in the formation of carbon-carbon Sp 2 Bonding, and , suggesting that both the selenium-selenium bonds of the selenium are under compression.
[0118] The compression caused by selenium immobilization is due to the carbon-carbon Sp 2 Bonding and The Se-Se bond in selenium is strengthened, and the Se-Se bond and the carbon-selenium bond are strengthened. This results in stronger Se-Se bonds and stronger carbon-selenium interactions. More kinetic energy is required for selenium to escape from the interaction, and this The T in immobilized selenium versus Se-Super P composite and Se-graphite composite Explain the reasons for the observed results of the GA analysis.
[0119] Furthermore, under compression, the carbon skeleton is better able to transfer electrons at the bond level. It is believed that under compression, the selenium atoms or molecules also have better electron transport capabilities. It is thought that this is the case.
[0120] Stabilization in immobilized selenium with improved electronic conductivity across the carbon backbone and selenium Selenium, for example, improves the specific capacity of the active material with minimal levels of shuttling, by immobilization In electrochemical processes, it is desirable to improve cycle performance and charge / discharge capability at high rates. However, this should not be construed in a limiting sense.
[0121] The X-ray diffraction pattern for the immobilized selenium prepared according to Example 10 shown in FIG. , the intensity of a broad diffraction peak from a carbon skeleton with a d-spacing of about 5.21 angstroms This is because the immobilized selenium further reduces the carbon skeleton. This suggests that the order of the carbon skeleton may be reduced or that the order of the carbon skeleton may be further disrupted. This is because the compressive force is carbon-carbon Sp 2 This is thought to be because it applies to bonding.
[0122] FIG. 14 shows an SEM image of immobilized selenium prepared according to Example 10, and the carbon of FIG. Similar to the skeleton image, it shows a sheet-like morphology. Approximately 50% of the selenium is immobilized in the carbon skeleton. However, except for the broken bonds between the sheets, there are no selenium particles on the surface of the carbon skeleton. No defects are observed and many flat sheets with high aspect ratios are obtained. These sheet-like forms have oriented coatings aligned along the direction of the flat sheet. It may be highly desirable to form a surface-to-surface contact of the sheet, This improves the electrical conductivity between the sheets, which makes it possible to electrochemically This can result in better electrical performance in the process.
[0123] Example 11: Preparation of Se cathode In a mortar and pestle, 56 mg of immobilized selenium prepared according to Example 10 and 7.04 mg of Super P and 182 μL of carboxymethylcellulose (CMC) solution (CMC Each 52 μL of solution contains 1 mg of dry CMC) and 21.126 μL of SBR latex. SBR latex dispersion (1 mg of dry SBR latex for every 6.036 μL of SBR latex dispersion) Add 200 μL of deionized water to the 100 μL PET bottle containing the particles, binder, and water. Manually grind the mixture into a slurry for 30 minutes to make the cathode slurry. The slurry was coated onto one side of a piece of conductive substrate, such as a foil, and allowed to air dry. The conductive substrate or foil may be an aluminum (Al) foil. However, any shape may be used. or any other suitable and / or desirable conductive material is contemplated. This should not be construed in a limiting sense. For purposes of illustration only, a selenium cathode is The use of Al foil to form the conductor will be described herein. However, this is a limitation. should not be construed in a definitive sense.
[0124] The Al foil coated with the slurry was then placed in a drying oven and dried at 55° C. for 12 hours. The selenium cathode was obtained by heating the aluminum foil for 10 min. The other side of the aluminum foil is uncoated, i.e. exposed aluminum. It is nium.
[0125] The selenium cathodes were then stamped into cathode disks each having a diameter of 10 mm. Some of these cathode disks were used as cathodes in secondary batteries.
[0126] Example 12: Assembly and testing of Li-Se secondary batteries The cathode disk from Example 11 was used to carry out the experiment shown in FIG. A Li-Se coin cell secondary battery was assembled as described in the Examples. The 10 mm diameter cathode disk 4 from Example 11 was placed in the positive case of a coin cell battery. The base of the 2032 stainless steel coin-shaped cell can, which acts as the “positive case” in Figure 15. The immobilized selenium sheet 5 faces upward away from the base 2 of the positive case, and is The exposed side of the cathode disk 4 faces and contacts the base 2 of the cathode case. A battery separator 6 (diameter 19 mm, thickness 25 μm) is placed in contact with the immobilized selenium sheet 5. In one example, the battery separator 6 is an organic separator, or an inorganic separator, or The separator may be a solid electrolyte. The organic separator may be a polymer, e.g., polyethylene. Polyethylene, polypropylene, polyester, halogenated polymers, polyethers, polyketones etc. The inorganic separator can be made from glass and / or quartz fibers.
[0127] Next, ethylene carbonate (EC) and dimethyl carbonate (DMC) solvents (by mass 50-50), 240 μL of electrolyte 7 containing LiPF6 (1M) was added to positive case 2 Then, a lithium foil plate is applied to the surface of the separator 6 opposite the cathode disk 4. Disk 8 (15.6 mm in diameter and 250 microns thick) was then placed on the lithium foil disk. A stainless steel (SS) spacer 10 is placed on the opposite side of the separator 6 of the disk 8, and then On the side of the SS spacer 10 opposite to the lithium foil disk 8, a nickel foam disk, for example, is One or more sheets of the lithium foil 8, the SS spacer 10, and / or the foam The disk 12 can function as an anode. The steel case 14 is used as the negative case for the coin cell (the “negative case” in Figure 15). In order to function, the nickel foam disk 12 is located on the opposite side of the SS spacer 10. The positive case 2 and the negative case 14 are then placed on the edge of the positive case 2. Then, the positive case 2 and the negative case 14 are placed under high pressure, e.g. The positive and negative cases (2, 14) were sealed together at high pressure. , cathode disk 4, separator 6, lithium foil 8, SS spacer 10, and Ni It also has the effect of compressing the laminate including the foam disk 12 (from bottom to top in FIG. 15) together. Using the battery separator and the fiberglass separator, more than a dozen coins were The assembled coin cell battery was then tested under the following conditions:
[0128] Using the Lanhe Battery Tester CT2001A, 0.1C and We tested some of the assembled coin cell batteries at a charge / discharge rate of 1C. The in-cell battery was tested as follows: (1) Rest for 1 hour. (2) Discharge to 1V. (3) 10 minutes. (4) Charge to 3V. (5) Rest for 10 minutes. For cycle testing, repeat step (2). Repeat ~(5).
[0129] FIG. 16A (left) shows the results of the experiment using the cathode prepared according to Example 11 and the cathode prepared according to Example 12. Cycle test results for the coin-type cell manufactured by this method (313 cycles at a charge / discharge rate of 0.1C) This shows good cycle stability, with a specific capacity of The specific capacity is 633.7mAh / g, which is a retention rate of 93.4% of the initial specific capacity. 1 The specific capacity of the second discharge is probably due to some side reactions on the cathode and anode surfaces. From the second cycle, the specific volume decreased with the cycle. However, the specific capacitance stabilized at about 180 cycles before decreasing again. The increase was slight from about 30 cycles to about 120 cycles. Excellent cycle stability for coin cells (100 cycles at 0.1C, then 100 cycles at 1C) At 600 cycles, the specific capacity was 462.5 mAh / g, which is is 66.0% retention of second cycle capacity at 0.1C or 1C The 105th cycle capacity retention is 80.3%. The coulombic efficiency is ≥ 95%. It can be as high as 98% or 100% and shuttles between the cathode and anode. This electrochemical performance suggests that the amount of selenium is not detectable in the cathode. This is the effect of immobilized selenium, which dissolves and moves from the cathode 14 to the anode 2. This is thought to prevent this.
[0130] FIG. 17 shows a coin assembled using the polymer separator described in Example 12. The size of the cells at various discharge-charge cycle rates (between 0.1C and 10C) was The test protocol is shown below. The test was the same as above, except for the C, 1C, 2C, 5C, and 10C. The charge / discharge cycle was performed for 5 cycles. Then, the cycle rate was returned to 0.1C. At a rate of 0.1C, the battery showed a specific capacity close to the stoichiometric value. Good cycle stability at cycle rates of 0.2C, 0.5C, 1C, and 2C The battery was cycled to 56% of its stoichiometric capacity at a 10C rate. They also exhibited fast charge and discharge capabilities, but showed a decrease in specific capacity with cycling. Then, at a 10C rate, the battery would need 56% of its stoichiometric capacity to be charged and discharged. It took 3.3 hours. At such a high cycle rate, the lifespan of a conventional battery is Life cannot be expected.
[0131] Li-Se cells containing immobilized selenium showed a 0.1C rate cycle at the start of the test. In this case, the capacity can be restored to 670mAh / g, or 98% of the total capacity. The stabilization of selenium in the stabilized selenium cathode is due to the fact that selenium leaves the carbon skeleton during cycling. This prevents selenium from traveling back and forth between the cathode and anode, This improves the cycle performance of the battery. (2) Sp 2 Carbon-carbon bonds and The carbon skeleton, the selenium-selenium bonds, and the carbon-selenium interactions are all under compression. This is possible because of the interactions within the carbon skeleton, within the selenium particles, and between carbon and selenium. This may result in superior electrical conductivity between the substrate and the substrate, which is consistent with the observed It is believed that this could help achieve better cycling performance.
[0132] The immobilized selenium bodies comprising selenium and carbon produced according to the principles described herein are The present invention may include one or more of the following features.
[0133] (a) The kinetic energy required for a selenium particle to detach from immobilized selenium is ≥ 9. 5 kJ / mol, ≧9.7 kJ / mol, ≧9.9 kJ / mol, ≧10.1 kJ / mol, ≧1 It can be 0.3 kJ / mol, or ≧10.5 kJ / mol.
[0134] (b) The temperature required for selenium particles to detach from the immobilized selenium is ≧490°C, ≧5 00°C, ≧510°C, ≧520°C, ≧530°C, ≧540°C, ≧550°C, or ≧560°C °C.
[0135] (c) Carbon is ≥ 500 m 2 / g, ≥ 600m 2 / g, ≥700m 2 / g, ≥800m 2 / g, ≥900m 2 / g or ≧1,000m 2 Surface area (20 Å) / g (for pores smaller than one mm).
[0136] (d) Carbon is less than or equal to 20%, less than or equal to 15%, less than or equal to 10%, less than or equal to 5%, less than or equal to 3%, less than or equal to 2% of the total surface area; ≦1% surface area (pores between 20 Å and 1000 Å) possible.
[0137] (e) The carbon and / or selenium may be under compression. Carbon and / or selenium systems where carbon and / or selenium are not under compression. The advantages of immobilized selenium under constriction are improved electron flow, reduced resistance to electron flow, or both, thereby forming a cathode made of immobilized selenium. Electron transfer from selenide anions to selenium during charging and discharging of secondary batteries containing This makes it easier to provide support.
[0138] (f) Since selenium is released from the immobilized Se-C complex, the immobilized selenium is Higher activation energy than the relatively high activation energy for (non-immobilized) selenium In one example, selenium having the formula: The activation energy for non-immobilized selenium (Se-Super P complex system) is 9 In contrast, in one example, immobilized selenium containing carbon was measured to have a selenium-selenium bond of 2 kJ / mol. The activation energies of selenium in toluene are ≥ 95 kJ / mol, ≥ 98 kJ / mol, and ≥ 101 kJ / mol, ≥ 104 kJ / mol, ≥ 107 kJ / mol, or ≥ 110 kJ / mol. In another example, the activation energy of selenium in immobilized selenium containing selenium and carbon may be increased. The activation energy of selenium in the Se-Super P composite is ≥ 3%, ≥6%, ≥9%, ≥12%, ≥15%, or ≥18% more likely.
[0139] (g) Immobilized selenium contains selenium with a higher collision frequency than non-immobilized selenium. In one example, the collision frequency of non-immobilized selenium can be determined according to ATSM method E1641-16 According to 5 In contrast, in one example, selenium and carbon The collision frequency of selenium in immobilized selenium containing 5 , ≧3.0×10 5 , ≧ 3.5×10 5 , ≧4.0×10 5 , ≧4.5×10 5 , ≧5.0×10 5 , ≧5.5× 10 5 , ≧6.0×10 5 , or ≥ 8.0 × 10 5 It is possible that immobilized selenium , ≥10%, ≥30%, ≥50%, and ≥8% higher than non-immobilized selenium in the Se-C composite. Collision frequency of 0%, ≥100%, ≥130%, ≥150%, ≥180%, or ≥200% may have.
[0140] (h) Immobilized selenium has a rate constant ≦1 / 5, ≦1 / 10, or Cells with a rate constant of ≦1 / 50, ≦1 / 100, ≦1 / 500, or ≦1 / 1000 In one example, the immobilized selenium can include ≦1×10 -10 , ≦5×10 - 11 , ≦1×10 -11 , ≦5×10 -12 , or ≦5×10 -13 The rate constant (50 It may contain selenium having a temperature of 30° C.
[0141] In the case of carbon and / or selenium of immobilized selenium under compression, the carbon (or is the carbon skeleton defined by the above carbons) Sp 2 In the Raman spectrum of the C-C bond The D-band and / or G-band in the -1 , ≧2cm -1 , ≥ 3cm -1 , ≥ 4cm -1 , or ≧ 5cm -1 , showing a red (positive) shift from the carbon source. obtain.
[0142] In the case of immobilized selenium carbon and / or selenium under compression, the selenium is ionized at a rate of 100% compared to pure selenium. Man Peak (235cm ―1 ) for example, ≧4cm ―1 , ≧6cm ―1 , ≧8cm ― 1 , ≧10cm ―1 , ≧12cm ―1 , ≧14cm ―1 , or ≧ 16cm ―1 The red color ( positive (positive) shift in the selenium content, suggesting a red shift in the selenium particles. do.
[0143] The immobilized selenium may be elemental selenium and / or compound selenium. .
[0144] The immobilized selenium, including selenium and carbon, may be, but is not limited to, sulfur and / or tellurium. One or more additional elements from Group 6 of the Periodic Table (hereinafter "additional G6 elements"), including The doping amount (dopant level) is 1 / 2 of the total mass of immobilized selenium. The concentration may range from as low as 0.00 ppm by weight to as high as 85% by weight. Immobilized selenium is made up of 15% to 70% carbon, 30% to 85% selenium, and optionally In one example, the immobilized selenium may contain (1) 15% to 7% of an additional G6 element. (1) 0% carbon and (2) 30% to 85% selenium, plus a mixture of additional G6 elements. In mixtures containing selenium plus additional G6 elements, the additional G6 elements are Selenium can make up 1% to 99.9% of the mixture. However, these ranges for selenium plus additional G6 elements are limited. should not be interpreted in any meaningful sense.
[0145] Immobilized selenium is ≥ 5% selenium, ≥ 10% selenium, ≥ 20% selenium, ≥ 30%, ≥ 40% selenium, ≥ 50% selenium, ≥ 60% selenium, or ≥ 70% selenium, or may contain more selenium.
[0146] The immobilized selenium may optionally contain other elements, such as sulfur, tellurium, and the like.
[0147] The immobilized selenium may be Raman inactive or Raman active. Stabilized selenium is 255±25cm -1 , 255±15cm -1 , or 255±10cm -1 The Raman relative peak intensity may be
[0148] The immobilized selenium has a Raman phase of ≥0.1%, ≥0.5%, ≥1%, ≥3%, or ≥5%. The Raman relative peak intensity can include selenium having a pair of peak intensities, and as used herein, the Raman relative peak intensity can be expressed as , the area of the D-band peak in the carbon Raman spectrum at 255 cm -1 Raman in It is defined as the area of the peak.
[0149] The carbon containing immobilized selenium can serve as a carbon skeleton for immobilization of selenium. The skeleton is 1365±100cm -1 The Raman D-band located at 1589±100c m -1 and the Raman G-band located at 2 - may have carbon-carbon bonds , 1365±70cm -1 and the D-band located at 1589±70 cm -1 Located in G - The band may have a length of 1365 ± 50 cm -1 D-band located at 1589± 50cm -1 and a G-band located at 1365±30 cm -1 Located in D-band and 1589±30cm -1 and a G-band located at 1365±20cm -1 and the D-band located at 1589±20 cm -1 Located in G- The second electrode may have a band.
[0150] The immobilized selenium on carbon has Raman peaks characterized by the D-band and the G-band. Sp 2 It can contain carbon-carbon bonds. The area ratio of the D-band to the G-band is Range 0.01 to 100, range 0.1 to 50, or range 0.2 to 20 may be in the range.
[0151] The immobilized selenium on carbon has Raman peaks characterized by the D-band and the G-band. Sp 2 Each of the D-band and G-band is Higher wave number ≧ 1cm -1 , ≧2cm -1 or higher.
[0152] The carbon of the immobilized selenium may be doped with one or more other elements of the periodic table. .
[0153] The carbon of the immobilized selenium may be porous. The pore size distribution of the carbon skeleton is within the range of 1 angstrom. The pore size distribution may range between 1 Angstrom and several microns. Between 1 and 100 Angstroms, and between 1 and 100 Angstroms Between 1 angstrom and 50 angstroms, Between 1 angstrom and 30 angstroms between 1 angstrom and 20 angstroms The porosity of the carbon skeleton may have at least one peak within the aforementioned range. It may have a multi-peaked pore size distribution.
[0154] The immobilized selenium on carbon was between 0.01 mL / g and 5 mL / g, and between 0.01 mL / g and 3 Between 0.03mL / g and 2.5mL / g, or between 0.05mL / g and 2.0 mL / g.
[0155] The immobilized selenium on carbon was determined to be 30%, >40%, >50%, or 10% of the total measurable pore volume. >60%, >70%, or >80% pore volume (<100 Å, <50 Å Angstroms, <30 Angstroms, or <20 Angstroms (including
[0156] Carbon of immobilized selenium is >400m 2 / g, >500m 2 / g, >600m 2 / g, > 700m 2 / g, >800m 2 / g, >900m 2 / g or >1000m 2 / g table It may include the area.
[0157] The carbon of the immobilized selenium may be amorphous and has a d of about 5.2 Angstroms. - may have a broad peak centered on the interval.
[0158] The immobilized selenium on carbon can be in any form, i.e., platelet, spherical, fibrous, needle-like, tubular, non-crystalline, or non-crystalline form. Regular, interconnected, aggregated, discrete, or any solid particle. Platelet-like, fibrous, needle-like, tubular, etc., having a given aspect ratio. Alternatively, certain morphologies may be advantageous for achieving better interparticle contact. This leads to improved electrical conductivity (throughout the immobilized selenium, which can be made with a variety of aspect ratios). This can be beneficial for electrochemical cell batteries, such as secondary batteries.
[0159] The carbon of the immobilized selenium is between 1-9 nanometers and 2 millimeters, Between 20 nanometers and <1000 microns, or between 20 nanometers and 100 microns The particles may be of any particle size, including dian particle size.
[0160] The selenium in immobilized selenium may be amorphous as determined by, for example, X-ray diffraction. The immobilized selenium can have a d-spacing of about 5.2 angstroms. The diffraction peak for the carbon skeleton may be weaker than the diffraction peak for the carbon skeleton, for example 10% weaker. It may be zero, 20% weaker, 30% weaker, or 40% weaker.
[0161] In one example, a method for producing immobilized selenium can include: (a) Physically mixing carbon and selenium. The physical mixing may be carried out using a ball mill (dry and wet). mixing with a mortar and pestle (dry or wet), jet mill, horizontal mill, grinding mill This can be achieved by mixing with high shear in the slurry, or by normal mixing with blades. Cut. (b) heating the carbon and selenium physically mixed in step (a) to a temperature above the melting point of selenium or Heating to a higher temperature is possible. Heating of the carbon and selenium mixture is not limited. However, in the presence of an inert gas environment such as argon, helium, or nitrogen, or in an air environment Alternatively, it can be carried out in a reaction environment. (c) If necessary, the heated carbon and selenium are mixed together to achieve immobilization of the selenium. and (d) cooling the immobilized selenium of step (c) to ambient or room temperature.
[0162] In another example, immobilized selenium was prepared by dissolving selenium on carbon and then evaporating it. The solvents that dissolve selenium include alcohol, ether, ester, Ketones, hydrocarbons, halogenated hydrocarbons, nitrogen-containing compounds, phosphorus-containing compounds, sulfur-containing compounds A mixture, water, etc. can be used.
[0163] In another example, selenium is melted onto carbon and then excess or surplus non-immobilized selenium is removed. By this, immobilized selenium can be produced.
[0164] In one example, a method for producing immobilized selenium includes: (a) mixing selenium and carbon together in a dry or wet state; (b) optionally drying the mixture of step (a) at elevated temperature. (c) optionally pelletizing the dried mixture of step (b). (d) A step of fusing selenium onto carbon to produce immobilized selenium.
[0165] The immobilized selenium can be used as a cathode material in secondary batteries. It may contain an inorganic binder or an organic binder. Inorganic binders are, for example, CMC. The cathode may be of natural origin, such as SBR rubber latex, or of synthetic origin, such as SBR rubber latex. For example, small particles derived from graphite, graphene, carbon nanotubes, carbon nanosheets, Optionally, a conductive promoter such as carbon black may be included. Finally, the cathode For example, a current collector such as aluminum foil, copper foil, carbon foil, carbon fiber, or other metal foil. may include.
[0166] The method for producing the cathode is to apply a slurry containing immobilized selenium onto a current collector, and then Dry the current collector after coating (e.g., air dry, oven dry, vacuum oven Drying, etc.) can be included. High shear mixer, regular mixer, planetary mixer Mixer, double planetary mixer, ball mill, vertical attritor, horizontal mill, etc. The immobilized selenium can be dispersed in the slurry prepared by the above method. After the coating is applied onto the current collector, it can be dried in air or in a vacuum. Prior to use in the pond, the coated cathodes are pressed or roller milled (or It can be processed by scanning the image.
[0167] The immobilized selenium described herein can be used to prepare a secondary battery. A cathode containing immobilized selenium, an anode, and a separator separating the anode and the cathode. The anode, cathode, and separator may be, for example, LiPF6 The anode can be immersed in an electrolyte such as lithium, sodium, silicon, or black. It may be composed of lead, magnesium, tin, etc.
[0168] The separator is composed of an organic separator, an inorganic separator, or a solid electrolyte separator. The organic separator may be, for example, polyethylene, polypropylene, polyester, Polymers such as halogenated polymers, polyethers, polyketones, etc. The separator may include glass fiber or quartz fiber, or a solid electrolyte separator. can be done.
[0169] The electrolyte is a lithium salt, a sodium salt, or IA, IIA, and The organic solvent may include organic carbonate compounds, acetone compounds, and other salts of Group IIIA. esters, alcohols, esters, hydrocarbons, halogenated hydrocarbons, lithium-containing solvents, etc. It can include.
[0170] Secondary batteries are used in electronic devices (electronics), electric or hybrid vehicles, and industrial The present invention may be used in aerospace, marine, and other applications, including military applications such as drones.
[0171] Secondary batteries have a selenium activity of ≧400mAh / g and a selenium activity of ≧450m Ah / g, ≥ 500mAh / g per selenium activity, ≥ 550mAh per selenium activity / g, or an electrochemical capacity per selenium activity of ≧600 mAh / g.
[0172] Secondary batteries: ≥ 50 cycles, ≥ 75 cycles, ≥ 100 cycles, ≥ 200 cycles and the like.
[0173] Secondary batteries are available in 0.1C, 0.2C, 0.5C, 1C, 1.5C, 2C, 3C, 4C, 5 C, 6C, 7C, 8C, 9C, 10C or faster. This is also fine.
[0174] The secondary battery was charged and discharged at a high C rate (5 cycles at 0.1C, 5 cycles at 0.2C). 5 cycles at 0.5C, 5 cycles at 1C, 5 cycles at 2C, 5 cycles at 5C, After 5 cycles at 10C, the specific capacity of the second discharge at a cycle rate of 0.1C >30%, >40%, >50%, >60%, >70%, or >80% of the battery specific capacity can be maintained.
[0175] Secondary batteries: ≥ 50%, ≥ 60%, ≥ 70%, ≥ 80%, ≥ 90%, or approximately 100% The coulombic efficiency of a battery can be defined as .
number
[0176] 0.1C, 0.2C, 0.5C, 1C, 1.5C, 2C, 3C, 4C, 5C, 6C, 7 The secondary battery can be charged at C, 8C, 9C, 10C or faster C rates. C rate is the rate at which a battery is discharged relative to its maximum capacity. For example, a 1C rate means that the discharge current will discharge the entire battery in 1 hour. For example, for a battery with a capacity of 100 amp-hrs, this is equivalent to a discharge of 100 amps. The 5C rate for this same battery would be 500 amps, and the 0.5C rate would be That would be 50 amps.
[0177] The cathode of a secondary battery is made of elements of the oxygen group (calcium oxide), such as selenium, sulfur, tellurium, and oxygen. The alloy may contain one or more elements of the fluorine group.
[0178] The anode of the secondary battery is made of alkali metals, alkaline earth metals, and Group IIIA metals. It may contain at least one element.
[0179] The separator of the secondary battery can include an organic separator or an inorganic separator.
[0180] The electrolyte of the secondary battery contains a small amount of alkali metals, alkaline earth metals, and Group IIIA metals. The electrolyte may contain at least one element, and the solvent may be a carbonate, ether, or can contain an ester-based organic solvent.
[0181] Secondary batteries: ≧400mAh / g, ≧450mAh / g, ≧500mAh / g, ≧55 The specific capacity may be 0 mAh / g or ≧600 mAh / g.
[0182] Secondary batteries: ≥ 50 cycles, ≥ 75 cycles, ≥ 100 cycles, ≥ 200 cycles and the like.
[0183] The secondary battery was charged and discharged at a high C rate (5 cycles at 0.1C, 5 cycles at 0.2C). 5 cycles at 0.5C, 5 cycles at 1C, 5 cycles at 2C, 5 cycles at 5C, After 5 cycles at 10C, the ratio of the second discharge at a cycle rate of 0.1C Specific capacity of >30%, >40%, >50%, >60%, >70%, or >80% of capacity may have the following structure:
[0184] The secondary battery has a coulombic efficiency of ≥ 50%, ≥ 60%, ≥ 70%, ≥ 80%, or ≥ 90%. may have the following structure:
[0185] Also disclosed is a complex comprising selenium and carbon, the complex having a molecular weight of ≧1, ≧2, ≧5, ≧10 , or may have a platelet shape with an aspect ratio of ≧20.
[0186] The selenium of the complex may be amorphous, for example as determined by X-ray diffraction. The diffraction peak of selenium can have a d-spacing of about 5.2 angstroms, and the diffraction peak of carbon can have a d-spacing of about 5.2 angstroms. The diffraction peak is weaker than that of the elementary skeleton, for example, 10% weaker or 20% weaker than that of the carbon skeleton. It may be 30% weaker or 40% weaker.
[0187] In one example, a method for producing a composite material includes: (a) Physically mixing carbon and selenium. The physical mixing may be carried out using a ball mill (dry and wet). mixing with a mortar and pestle (dry or wet), jet mill, horizontal mill, grinding mill, This can be done by high shear mixing in the slurry, normal slurry mixing with blades, etc. . (b) subjecting the physically mixed carbon and selenium of step (a) to a temperature at or above the melting point of selenium; The heating can be performed in an inert gas atmosphere such as argon, helium, nitrogen, etc. The reaction can be carried out in the presence of a neutral environment, or in air or in a reactive environment. , (c) reacting the heated carbon and selenium of step (b) with a catalyst to aid in achieving immobilization of the selenium. As such, it can be homogenized or blended.
[0188] In another example, a composite material was made by dissolving selenium on carbon and then evaporating it. Solvents that dissolve selenium include alcohols, ethers, esters, and ketones. , hydrocarbons, halogenated hydrocarbons, nitrogen-containing compounds, phosphorus-containing compounds, sulfur-containing compounds, Water, etc.
[0189] After the selenium is melted onto (or into) the carbon, the excess or surplus non-immobilized selenium is removed. By removing the ions, a composite can be produced.
[0190] In one example, a method for producing a composite material includes: (a) mixing selenium and carbon together in a dry or wet state; (b) optionally drying the mixture of step (a) at elevated temperature. (c) optionally pelletizing the dried mixture of step (b). (d) A step of dissolving selenium in carbon to produce immobilized selenium.
[0191] The composite material can be used as a cathode material for the cathode of a secondary battery. The binder may be an inorganic or organic binder. The inorganic binder may be, for example, CMC. It may be any natural or synthetic material, such as SBR rubber latex. Examples of the dopants include small particles derived from graphite, graphene, carbon nanotubes, and carbon nanosheets. Optional conductivity promoters such as carbon black may be included. The cathode may be, for example, a composite of aluminum foil, copper foil, carbon foil, carbon fiber, or other metal foil. It may include an electric field.
[0192] The method for preparing the cathode is to apply a slurry containing immobilized selenium onto a current collector, After that, the current collector after the slurry application is dried (e.g., air dried, oven dried, vacuum dried, etc.). Oven drying, etc.) can be included. Netary mixer, double planetary mixer, ball mill, vertical attritor, horizontal The immobilized selenium can be dispersed in a slurry that can be produced by a mill or the like. Next, the slurry is applied onto the current collector and then dried in room air or in a vacuum. Prior to use in a secondary battery, the coated cathode can be subjected to a pressure treatment or roller mill. It can be treated (or calendared).
[0193] The above composite material can be used to fabricate secondary batteries. C, 1C, 1.5C, 2C, 3C, 4C, 5C, 6C, 7C, 8C, 9C, 10C, or It can charge secondary batteries faster.
[0194] Example 13: Preparation of immobilized selenium doped with sulfur, electrodes, and batteries thereof. According to the principles and procedures described in Example 10, the sulfur doped solids detailed in Table 4 were obtained. In the synthesis of stabilized selenium, 5 atomic % selenium, 20 atomic % selenium, 35 atomic % selenium, and 50 atomic percent of selenium was replaced by sulfur. A sample of selenium chloride was synthesized using a carbon skeleton prepared according to the principles and procedures described in Example 9. Successful.
[0195] [Table 4]
[0196] The thus prepared sulfur-doped immobilized selenium sample was then used to According to the principles and procedures described in Example 11 relating to the present invention, a multi-layer structure including immobilized sulfur-doped selenium was prepared. A number of cathodes 4 were manufactured.
[0197] The sulfur-doped immobilized selenium thus produced in this example was then Using the cathode, a coin cell battery was constructed according to the principles and procedures described in Example 12. was manufactured.
[0198] The coin cell battery assembled in this example was subjected to the battery test described in Example 12. The machine was charged and discharged at 0.1C and 1C according to the same test protocol described in Example 12. The test was performed at a constant current cycle rate.
[0199] The sulfur-doped immobilized selenium sample (Se50S50 in Table 4) was used. The electrochemical performance of the coiled battery containing the cathode made of the ferroelectric cathode at 0.1C was The results of the second cycle are shown in Figure 18. Here, the second cycle discharge capacity was 821 mAh / g (which is considered good) and the steady-state coulombic efficiency is ≥ 95%, typically ≥ 98% (considered good), or as high as 100%.
[0200] Assuming that selenium has a stoichiometric specific capacity of 675 mAh / g at a cycle rate of 0.1C, This gives a sulfur specific capacity of about 1,178 mAh / g (considered to be good for sulfur). Coulombic efficiencies of ≥ 95%, ≥ 98%, or even as high as 100% are estimated. This shows that no significant amount of sulfur shuttles between the cathode and anode. The sulfur species in lithium batteries perform well in electrolytes containing carbonates. Typically However, sulfur works well in Li-S batteries with carbonate as the electrolyte. Conventional Li-S batteries typically use ether-based electrolytes. Carbonate-based electrolytes are typically used in the present lithium-ion batteries. Compared with ether-based electrolytes, nate-based electrolytes are more economical and have a higher market share. It is more widely used.
[0201] The sulfur-doped immobilized selenium sample (Se50S50 in Table 4) was used. For coil cell batteries containing cathodes constructed with RenCo cathodes, 1C cycle rate The electrochemical cycling results are shown in Figure 19. Here, the second cycle discharge capacity was 72 4 mAh / g and a steady-state coulombic efficiency of ≥ 95%, typically ≥ 98%, or It is as high as 100%.
[0202] Assuming that selenium has a specific capacity of 625 mAh / g at 1C cycling rate, sulfur The specific capacity is estimated to be about 966 mAh / g (also unexpected). Li-S batteries are usually used at high rates such as 1C. It does not cycle well at fast cycle rates.
[0203] As described above, when used as a cathode material for secondary batteries, the sulfur-doped immobilized selenium The study addressed two fundamental problems associated with Li-S batteries: the shuttle effect and low cycle rate. By solving these two problems, the sulfur-doped immobilized selenium can be Batteries containing cathodes made of ZnO have the potential to provide high energy density and high current in practical applications. and a force density.
[0204] As described above, in one example, the sulfur-doped immobilized selenium system or the sulfur-doped immobilized selenium body (a) mixing selenium, carbon, and sulfur to form selenium; (b) heating the mixture of step (a) to a temperature higher than the melting point of selenium; (c) heating the heated mixture of step (b) to ambient or room temperature. cooling, thereby forming sulfur-doped immobilized selenium bodies.
[0205] The sulfur-doped immobilized selenium body of step (c) contains selenium and sulfur in a carbon skeleton. can.
[0206] Step (a) can be carried out under dry or wet conditions.
[0207] Step (b) may include homogenizing or blending the mixture.
[0208] Step (a) may include forming the selenium-carbon-sulfur mixture into a body. Step (b) includes heating the body to a temperature above the melting temperature of selenium. Step (c) may include cooling or allowing the body to cool to ambient or room temperature. This may include making the device capable of
[0209] Step (b) is a step of mixing the selenium with carbon and sulfur for a period of time sufficient to completely or partially react the selenium with carbon and sulfur. The method may include heating the mixture.
[0210] In another example, a method for producing a sulfur-doped immobilized selenium system or a sulfur-doped immobilized selenium body is provided. (a) forming a carbon skeleton; and (b) dissolving selenium and sulfur in the carbon skeleton. About.
[0211] In another example, a method for producing a sulfur-doped immobilized selenium system or a sulfur-doped immobilized selenium body is provided. The present invention relates to a process for producing a selenium-based composite oxide, comprising the steps of: (a) mixing selenium, carbon, and sulfur; and (b) after step (a), The selenium and sulfur are dissolved in carbon, thereby forming a sulfur-doped immobilized selenium system or a sulfur-doped solid making a stabilized selenium body.
[0212] Solvents for dissolving selenium and sulfur include alcohols, ethers, esters, ketones, Hydrocarbons, halogenated hydrocarbons, nitrogen-containing compounds, phosphorus-containing compounds, sulfur-containing compounds, or The selenium, sulfur, etc. may be added before step (a), during step (a), or during step (b). A solvent can be added to one or more of the following: yellow, or carbon.
[0213] The method further comprises: (c) adding an excess of non-immobilized selenium, non-immobilized sulfur, or both, to a sulfur dopant. The method may further comprise removing the sulfur-doped immobilized selenium from the immobilized selenium system or the sulfur-doped immobilized selenium body. Cut.
[0214] A cathode composed of sulfur-doped immobilized selenium disposed on a conductive substrate; a separator disposed in direct contact with the sulfur-doped immobilized selenium and in contact with the sulfur-doped immobilized selenium; Also disclosed is a secondary battery including an anode separated from a cathode by a capacitor.
[0215] The secondary battery may further include an anode separated from the separator by lithium. In one example, the lithium can be in the form of lithium foil.
[0216] The secondary battery further includes a cathode immersed in an electrolyte, a separator, an anode, and It may contain lithium.
[0217] In secondary batteries, sulfur-doped immobilized selenium is a selenium-based material in which selenium and sulfur are fused to carbon. The carbon-sulfur mixture may include
[0218] In a secondary battery, the separator is made of an organic material, an inorganic material, or a solid electrolyte. It may be possible.
[0219] The secondary battery may have a coulombic efficiency of ≧95%.
[0220] These examples are described with reference to the accompanying drawings. Upon reading and understanding the foregoing examples: Modifications and variations to other examples are possible. Accordingly, the above examples are not intended to limit the present disclosure. should not be construed as an
Claims
1. a cathode constituted by a composite material disposed on a conductive substrate, the composite material being made of selenium under compression doped with sulfur and immobilized in a carbon skeleton; a lithium-containing anode separated from the cathode by a separator; The separator is formed from an organic material, an inorganic material, or a solid electrolyte; and The collision frequency of selenium in the composite material is ≧2.5×10 5 That is, a secondary battery.
2. 2. The secondary battery according to claim 1, wherein the composite material contains selenium:sulfur in an atomic percent range of 50:50 to 95:
5.
3. 2. The secondary battery according to claim 1, wherein the composite material contains selenium:sulfur in an atomic percent range of 65:35 to 80:
20.
4. 10. The secondary battery of claim 1, wherein the anode is separated from the separator by lithium.
5. 5. The secondary battery of claim 4, wherein the cathode, the separator, the anode, and the lithium are immersed in an electrolyte.
6. The secondary battery according to claim 5 , wherein the electrolyte is a carbonate-based electrolyte.
7. 7. The secondary battery according to claim 6, wherein the carbonate-based electrolyte is one or more of diethyl carbonate, dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, and propylene carbonate.
8. 10. The secondary battery of claim 1, wherein the secondary battery has a coulombic efficiency of ≧95%.
9. 10. The secondary battery of claim 1, wherein the secondary battery has a coulombic efficiency of ≧98%.
10. The secondary battery of claim 1 , wherein the secondary battery is in the form of a coin cell battery.
11. The collision frequency of selenium in the composite material is ≧3.0×10 5 The secondary battery according to claim 1 ,
12. 2. The secondary battery of claim 1, wherein the kinetic energy for detachment of selenium particles from the composite material is ≧9.5 kJ / mol.
13. The secondary battery of claim 1 , wherein the carbon skeleton is two-dimensional.
14. 2. The secondary battery of claim 1, wherein the carbon skeleton is amorphous.
15. The secondary battery of claim 1 , wherein the carbon skeleton is porous.
16. 2. The secondary battery according to claim 1, wherein the carbon skeleton has a sheet-like or platelet-like shape.
Citation Information
Patent Citations
Selenium-micropore carrier composite, preparation method and application thereof
CN103187559A
Novel secondary battery cathode sulfur and selenium binary material and preparation method
CN104617299A
Preparation method and application of selenium-carbon compound
CN105070892A
Electrode materials for rechargeable batteries
US20120225352A1